Estratégias de extração e espessura de amostras para avaliação visual da estrutura do solo - Pacheco, Vacilania (2020)
The objective of this work was a) to evaluate whether different thicknesses of the samples result in changes in the structural quality index (Sq) of the soil by the VESS method b) to test different sample extraction tools to proceed with the evaluation of the Sq-VESS and c) to evaluate different exposure strategies of soil aggregates during VESS assessment; in basaltic clayey Oxisols. The thickness evaluations of the samples were made in areas under no-tillage in Guarapuava, Pato Branco and São Jorge do Ivaí. Ten samples of 15 x 25 cm (width and depth) were taken in each area, with a straight shovel, in thicknesses: 5; 10; 15; 20 and 25 cm. The assessments of the extraction tools were carried out in three areas in Pato Branco, taking ten samples for each of the tools: cutting shovel; shovel + mallet + wood; impact shovel; garden shovel; pitchfork; chainsaw and shovel attached to a tractor. In the same places where the tools were evaluated, three disaggregation strategies were evaluated: manual; striking the shovel with a sledgehammer; and to hit the shovel on the floor, totaling 30 samples. The Sq score and practical aspects of sample extraction were evaluated. Samples with a thickness of 5 cm showed lower Sq due to the reduction of aggregates by cutting through the shovel. For samples with a thickness of 20 cm, there was greater difficulty in extraction. Extracting 10 cm samples was more practical when compared to 15 cm samples (standard method), due to the smaller volume of soil extracted. It was not possible to evaluate the Sq score in 25 cm thick samples due to the great difficulty in extracting the sample. The integrity of the samples is preserved with the use of an impact shovel and chainsaw, while the blade coupled to the tractor produced great compaction on the sides and the lower portion of the sample. The use of shovel + mallet + wood caused disruption in the upper portion of the sample. The garden shovel and pitchfork tools did not allow sample extraction. Disaggregating the soil by tapping the shovel with the mallet or on the ground promoted soil dispersion and mixing of the layers. The results suggest that the extraction of samples with a thickness of 10 cm can also be used to obtain the Sq score. The best method for extracting the sample is with the cutting shovel, the impact shovel and the chainsaw and; the recommended technique for isaggregation is manual.